Site directed mutagenesis of miRNA binding site on the 3′-UTR of choline kinase alpha gene - Bnisallama, Faisal Fayez Saffah (2022)
MicroRNA largely controls gene expression by attaching to messenger RNA (mRNA) in the cell cytoplasm. Instead of being promptly translated into a protein, the targeted mRNA will either be destroyed and its components recycled, or it will be retained and translated later. Choline kinase alpha (chka) overexpression is a clinical sign of diseased tissues and malignant cells. MicroRNAs (miRNAs) are effective posttranscriptional regulators of gene. Studies by our team showed that these three miRNAs (miR-876-5p, miR-367-3p and miR-32-5p) downregulated the expression of chka gene. However, the binding sites of these miRNAs on the 3'-UTR of the chka gene have not been verified. This study aimed to mutate the binding sites of these miRNAs for subsequent verification by a luciferase assay. In this study, we performed PCR site-directed mutagenesis on the miR-367-3p (GAAGCAGAAAT ATAGTGCAATA) from nucleotides (nt) 1817-1825 binding sites in chka and miR-876-5p (GAG TGTAGCTGTG AAATCCA) binding site from nucleotides (nt) 2573-2581 binding sites and verified the mutation by DNA sequencing. In vitro work, after mutagenesis step, the PCR products were sent for sequencing, however the results were not satisfactory.